Potential of bacteria in sheep feces as biogas formation starter on lignite coal media - Yuli Astuti Hidayati; Marlina ET; Rahmah KN; Pinandito K; Puteri GCK; Harlia E (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
Sheep farms produce waste in the form of feces and urine that are organic materials and the source of bacteria. This study aims to determine the potential of bacteria in sheep feces when used as a starter for biogas formation (the number of anaerobic bacteria and biogas production) on lignite coal media. The method used in this study was experimental in the laboratory using a completely randomized design with four treatments and four replications. The data were analyzed using analysis of variance, and Duncan test was performed to find out the differences between treatments. The research procedure was divided into two stages. The first stage was in vitro method to select the feces sample with the largest biogas production. The second stage was utilizing enriched media (media 98-5) liquid for observing the growth of bacteria originating from selected sheep feces, and then the bacteria consortium was used as starters on lignite coal media. The treatments were based on the concentration of bacteria consortium used, T1=0%, T2=1.5%, T3=3%, and T4=4.5%. The number of anaerobic bacteria was observed in Hungate tubes, and biogas production was observed in serum bottles. The results showed that the highest number of anaerobic bacteria (1012 CFU/ml) and the highest biogas production (105 mL) were achieved at T2=1.5%. Bacteria in sheep feces can be potentially used as a biogas forming agent on lignite coal media, which is proved by the growth of anaerobic bacteria and the biogas production from present study.